Development of Store Atmosphere on Culinary Efforts increase Interest In The Buying Public, in District of Percut Sei Tuan - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Hasil Penilaian Sejawat Sebidang Atau Peer Review Karya Ilmiah : Buku Development of Store Atmosphere on Culinary Efforts increase Interest In The Buying Public, in District of Percut Sei Tuan